Production of metal and dielectric films in a combined RF and arc discharge - Gasilin, V.V.; Kunchenko, V.V.; Nezovybat’ko, Yu.N.; Taran, A.V.; Taran, V.S.; Tereshin, V.I.; Shvets, O.M. (Вопросы атомной науки и техники, 2003)
In the presentation we investigate the possibilities to deposit metallic and dielectric films on metal and dielectric materials by means of vacuum technology with application of high frequency (RF) electric fields. As a base-model the device “Bulat-6” was used with proper arc evaporators. The leading-in of a RF power (3 kW, f=1-10 MHz) was realized by connecting the RF generator to a planyclic system of the device. Before the film deposition the samples were conditioned by plasma of RF discharge (without arc discharge) at the gas pressure p=10⁻⁴ Torr. The multi-layer coatings of the type Cr-CrN, Cr-TiN-Cr, Ti-TiN-Ti deposited on complicated shape wares of aluminum alloys had a microhardness value up to 2000 kg/mm². The properties of such coatings were studied depending on the vacuum conditions in the process of deposition. Taking into account the potential well developing under RF field, the experiments were provided on depositing the drip-free coatings by placing the wares in that region of vacuum chamber, which is closed from the direct ingress of particles from the arc vaporizer. The Al₂O₃ and AlN dielectric coatings were obtained and their characteristics were studied by using the electron microscope technique. Вивчались можливості нанесення металевих i діелектричних плівок на метали й діелектрики в вакуумі з застосуванням високочастотних (ВЧ) електричних полів. Експерименти проводились на установці “Булат-6” . Підвід ВЧ енергії (3кВТ, f =1-10мГц) було здійснено шляхом підключення ВЧ-генератора до поворотного пристрою установки. Перед нанесенням плівок поверхня зразків оброблялась плазмою газового ВЧ-розряду (без дугового розряду) під тиском p=10⁻⁴ Toр. Багатошарові покриття складу Cr-CrN, Cr-TiN-Cr, Ti- TiN-Ti, осаджувані на вироби різних форм із сплавів алюмінію, мали мікротвердість до 2000кГ/мм². Вивчалась залежність властивостей таких покриттів від вакуумних умов під час осадження. Хороше проникнення ВЧ-електричного поля в плазму давало можливість одержувати покриття без макрочастинок за рахунок розміщення зразків в місцях вакуумної камери, куди макрочастинки з дугового випаровувача не попадали. Одержано також діелектричні покриття Al₂O₃ й AlN. Їх характеристики досліджувались за допомогою методів електронної мікроскопії. Исследованы возможности осаждения металлических и диэлектрических пленок на металлы и диэлектрики при помощи вакуумной технологии с применением высокочастотных (ВЧ) электрических полей. Эксперименты проводились на установке “Булат-6”. Подвод ВЧ энергии (3кВт, f = 1-10мГц) обеспечивался подключением ВЧ-генератора к поворотному устройству установки. Перед нанесением покрытий образцы подвергались воздействию плазмы высокочастотного газового разряда (в отсутствие дугового разряда) при давлении p=10⁻⁴ Toр. Многослойные покрытия Cr-CrN, Cr-TiN-Cr, Ti-TiN-Ti, осажденные на изделия различной формы из алюминиевых сплавов имели микротвердость до 2000 кГ/мм². Исследованы свойства этих покрытий в зависимости от вакуумных условий процесса осаждения. Учитывая хорошее проникновение высокочастотного электрического поля в плазму, были выполнены эксперименты по нанесению покрытий, не содержащих макрочастиц, путем помещения изделий в те части вакуумной камеры, куда макрочастицы из вакуумно-дугового испарителя не попадают. Получены, также, диэлектрические покрытия Al₂O₃ и AlN. Их свойства исследованы с помощью методов электронной микроскопии.